APPROACHES TO THE DEVELOPMENT OF THE TOURISM INDUSTRY (Marketing Journal, 2025)
The development of the tourism industry is one of the strategic directions of the modern economy, and its socio -economic significance is increasing day by day. This article provides a scientific analysis of the necessity for the development of the tourism industry, its existing opportunities, and its key advantages. The study examines the impact of tourism on the economy, its interconnection with society and the environment, and approaches aimed at forming a sustainable development model. Furthermore, the p aper explores international experiences in tourism development by analyzing the successful strategies of developed countries and assessing their 140 adaptability to local conditions. Based on the findings, scientific and practical recommendations are formulated, and conceptual approaches to improving the tourism sector are proposed.
Keywords: tourism; industry; approach; tourism industry; product; service; economy